2014
DOI: 10.3382/ps.2013-03368
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of in-feed preparations of an anticoccidial, multienzyme, prebiotic, probiotic, and herbal essential oil mixture in healthy and Eimeria spp.-infected broilers

Abstract: The efficacies of 5 widely used dietary supplements were investigated on performance indices, fecal oocyst excretion, lesion score, and intestinal tract measurements in healthy and Eimeria spp.-infected birds by using a comparative model. This study included 2,400 sexed Ross 308 broiler chicks that were equally divided in 2 groups: the infected group, experimentally infected with oocysts of mixed Eimeria spp. at 14 d of age, and the healthy controls. The birds in both groups were further divided equally into 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
49
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(64 citation statements)
references
References 47 publications
7
49
0
2
Order By: Relevance
“…In recent literature [22] it has been reported that common in-feed performance enhancers, including essential oils of medicinal herbs, can potentially replace antimicrobials in broiler nutrition. According to those authors, scientific evidence has shown that these additives can be used to improve the intestinal health of broilers, mainly when different types of challenge are present, to avoid subclinical diseases.…”
Section: Productive Performancementioning
confidence: 99%
“…In recent literature [22] it has been reported that common in-feed performance enhancers, including essential oils of medicinal herbs, can potentially replace antimicrobials in broiler nutrition. According to those authors, scientific evidence has shown that these additives can be used to improve the intestinal health of broilers, mainly when different types of challenge are present, to avoid subclinical diseases.…”
Section: Productive Performancementioning
confidence: 99%
“…Although these are effective, the development of drug resistance and consumer concerns about chemical residues in poultry products have caused a decrease in the use of anticoccidial drugs (Quiroz-Castaneda and Dantan-Gonzalez, 2015). The use of natural alternatives such as fats, antioxidants, essential oils, herbal extracts, prebiotics, and probiotics have shown some promise in ameliorating the negative effects of coccidiosis (Bozkurt et al, 2014;QuirozCastaneda and Dantan-Gonzalez, 2015). The cost of production, however, of these natural alternatives is currently high, but the cost can be offset by increased performance and use of a more environmental and consumer friendly product.…”
Section: Introductionmentioning
confidence: 99%
“…When birds are reared under suboptimal experimental conditions, feed additives are more efficient (Orban et al, 1997). Growth-promoting effects of probiotic and prebiotic were more pronounced under coccidial challenge conditions rather than under unchallenged conditions (Bozkurt et al, 2014). In addition, it is reported that under clean or hygienic condition, broilers do not need any feed additives for maximum growth (Baurhoo et al, 2009).…”
Section: Performance and Cecal Bacteria Counts Of Broilers Fed Low Prmentioning
confidence: 99%
“…Supplementation with probiotics and prebiotics can improve the performance of broiler chickens (Kim et al, 2011;Yang et al, 2012;Houshmand et al, 2012b;Salim et al, 2013;Bozkurt et al, 2014). Also, their positive effects on protein utilization have been indicated.…”
Section: Introductionmentioning
confidence: 99%